Perempuan dan Media: Representasi Pewarta pada Rubrik Jurnalisme Warga Harian Serambi Indonesia - Ulfa Khairina (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research examines women and media in journalistic activities. One way is to become journalistic activities. One way to become of a citizen journalist in the Serambi Indonesia daily. The Serambi Indonesia daily based in Banda Aceh is a large-circulation local media that has access to citizen journalists through the Citizen Journalism colomn. This reseacrh uses a descriptive qualitative approach. Data collection was carried out by documenting articles written by female journalists. The research results show that female journalists in the Citizen Journalism column write by involving their experiences in an event with the construction of article writing in accordance with news elements.